2017
DOI: 10.1177/1098612x17746282
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of the presentation, diagnosis and management of 16 cats with otitis media not due to nasopharyngeal polyp

Abstract: This small cohort shows that some cats with OM can be successfully managed medically. Surgery is invasive and may not necessarily be required if appropriate medical management is undertaken. This is the first study of OM treatment in cats and provides the basis for further studies, which should aim to establish specific infectious causes of OM and how they can potentially be managed with medical therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 15 publications
0
19
1
Order By: Relevance
“…12,13,26 Otitis media/interna was diagnosed when compatible changes, affecting the middle and inner ear, were identified on MRI or CT imaging and further supported by otoscopy and myringotomy when performed. 9,19,27 A middle ear polyp diagnosis was considered when advanced imaging demonstrated a pedunculated, well-demarcated, soft tissue mass in the region of the nasopharynx. 10,11,28,29 Intracranial empyema was diagnosed based on the combination of compatible MRI findings and CSF abnormalities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13,26 Otitis media/interna was diagnosed when compatible changes, affecting the middle and inner ear, were identified on MRI or CT imaging and further supported by otoscopy and myringotomy when performed. 9,19,27 A middle ear polyp diagnosis was considered when advanced imaging demonstrated a pedunculated, well-demarcated, soft tissue mass in the region of the nasopharynx. 10,11,28,29 Intracranial empyema was diagnosed based on the combination of compatible MRI findings and CSF abnormalities.…”
Section: Methodsmentioning
confidence: 99%
“…5,6 Accurate neuroanatomical localisation can aid the clinician in formulating a prioritised list of differential diagnoses, determining a diagnostic plan and prognostication, with causes of central vestibular syndrome having been attributed, in referral hospital populations, with a poorer prognosis than peripheral disease. 5,7 Idiopathic vestibular syndrome and otitis media/interna are widely regarded as the most frequent causes of peripheral vestibular syndrome in cats, 3,6,8,9 with neoplastic lesions of the middle ear also reported. 10,11 Central vestibular syndrome has been reported secondary to intracranial neoplasia, 5 feline infectious peritonitis (FIP), 12,13 ischaemic infarcts, 14,15 thiamine deficiency 1618 and intracranial empyema.…”
Section: Introductionmentioning
confidence: 99%
“…Medical management for bacterial otitis with neurological signs, respiratory signs and thickened bulla wall not due to a nasopharyngeal polyp was reported to be sufficient to resolve clinical signs 14) , but medical management for the presented case did not resolve clinical signs. Post-operative complications after bulla osteotomy have been reported to include Horner's syndrome, paralysis of the facial nerve and otitis interna 15) .…”
Section: Discussionmentioning
confidence: 66%
“…Less commonly, otitis media occurs as an extension of otitis externa and it also has been suggested that a potential cause could be haematogenous spread. 5 The clinical signs of otitis media overlap with otitis externa. This can make the diagnosis challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Otitis media in cats most commonly presents as a result of a nasopharyngeal polyp (NPP), from pharyngeal or upper respiratory infection which has extended up through the auditory (Eustachian) tube, following auditory tube dysfunction or obstruction, or associated with a sterile mucositis/sinusitis. Less commonly, otitis media occurs as an extension of otitis externa and it also has been suggested that a potential cause could be haematogenous spread 5 …”
Section: Introductionmentioning
confidence: 99%